Time-lapse sonic logs reveal patchy CO2 saturation in-situ - Caspari, Eva; Müller, T.; Gurevich, Boris (American Geophysical Union, 2011)
Based on time-lapse sonic and neutron porosity logs from the Nagaoka CO2 sequestration experiment, a P-wave velocity-saturation relation at reservoir depth is retrieved. It does not coincide with either of the end-member models of uniform and patchy saturation but falls in between even if realistic error estimates for the host rock properties are considered. Assuming a random distribution of CO2 patches it is shown that the mechanism of wave-induced flow can be evoked to explain this velocity-saturation relation. Characteristic CO2 patch size estimates range from 1 to 5 mm. Such mesoscopic heterogeneity can be responsible for attenuation and dispersion in the well logging frequency band.